The Effectiveness Of Sweet Fennel Administration On Increasing Breast Milk Production In Breastfeeding Mothers : Breastfeeding Mothers - Setia Sihombing; Ucy Tryaningsih; Tri Suci Dewiwati (Jurnal Penelitian Pendidikan IPA, 2026)
Exclusive breastfeeding during the first six months is crucial for infant growth and health. However, various studies have shown that a considerable number of mothers experience inadequate breast milk production. One non-pharmacological approach to address this issue is the use of fennel (Foeniculum vulgare), which contains anethole with estrogenic and galactagogue properties that can stimulate the hormones prolactin and oxytocin. This study aimed to evaluate the effectiveness of fennel tea in increasing breast milk production. An experimental design with a paired sample t-test was employed. Breast milk volume and prolactin hormone levels were measured before fennel tea administration (pre-test) and after four weeks of fennel consumption (post-test). The study sample consisted of five breastfeeding mothers aged 2–21 days postpartum, selected through accidental sampling. The paired sample t-test results showed a statistically significant increase in breast milk volume (t = -53.733, p < 0.001) and prolactin levels (t = -3.079, p < 0.037). These findings provide scientific evidence supporting the use of fennel as a natural galactagogue to enhance breast milk production through hormonal and physiological mechanisms. It can be concluded that fennel tea significantly increases breast milk volume and prolactin hormone levels in breastfeeding mothers.